Technological advances in obtaining, identifying and producing protein hydrolysates from fish residues by enzymatic action: bioactive and techno-functional properties, application in food, market and regulation - Espinoza, Deyvis (2022)
At present, numerous methodologies have been developed to obtain the maximum use of fish proteins, to satisfy human nutritional demand, this use has been made both from whole fish and from its residues or by-products (liver, head, skin, gonads, skeleton, and viscera) which represent up to 60% of the whole fish. Whole fish and by-products can potentially be used as sources of essential amino acids, collagen, gelatin, polyunsaturated lipids, and enzymes. Using enzymatic technology, protein hydrolysates have been obtained with ample potential for their application as ingredients in the development and production of fortified foods, due to their functional properties (antihypertensive, antioxidant, antimicrobial and immunomodulatory), which can reduce the risk of cancer, aging, diabetes, and cardiovascular diseases. In addition, these hydrolysates have important techno-functional properties (foaming, solubility, emulsification, gelation, water, and oil retention) that provide desirable technological characteristics for processing, storage and product quality, as well as for behavior during processing. and storage. This review analyzes the advances in the technology for obtaining, identifying, and producing fish protein hydrolysates (FPH) by enzymatic action, with an emphasis on fish residues, highlighting the application of FPH in food, market analysis and global regulations. It is recommended to continue the studies to optimize the enzymatic production of FPH to improve the flavor and its application in the fortification of mass consumption foods.